A new and highly divergent mitochondrial lineage in the Small Five-toed Jerboa, Allactaga elater, from Iran (Mammalia: Rodentia). Issue 3 (2nd July 2016) - Mohammadi, Saeed; Afonso, Sandra; Adibi, Mohammad Ali; Melo-Ferreira, José; Campos, Rita
Abstract : The Small Five-toed Jerboa, Allactaga elater, is a small rodent adapted to desert and semi-arid habitats with a widespread distribution around the Caucasus. Previous studies have suggested the occurrence of subspecific variation within the species but, except for a recent phylogeny of the genus Allactaga, most of the work done on the taxonomy of the group relies on morphological data only. To contribute to the current understanding of patterns of genetic diversity of A. elater we analysed one mitochondrial locus, cytochrome b, from 13 Iranian specimens. Comparing to a recent phylogeny, our results suggest the existence of two additional mitochondrial lineages, one that clusters within previously described lineages and a new and highly divergent one. The two novel mitochondrial lineages occur in the north and form two highly divergent monophyletic groups (Dxy = 14%), which likely separated during the Pleistocene.